CXCL12/CXCR4 signaling contributes to neuropathic pain via central sensitization mechanisms in a rat spinal nerve ligation model - Liu, Zhi‐Yuan (CNS Neurosci Ther, 2019)
BACKGROUND: Previous studies have demonstrated that the CXCL12/CXCR4 signaling axis is involved in the regulation of neuropathic pain (NP). Here, we performed experiments to test whether the CXCL12/CXCR4 signaling pathway contributes to the pathogenesis of neuropathic pain after spinal nerve ligation (SNL) via central sensitization mechanisms. METHODS: Neuropathic pain was induced and assessed in a SNL rat model. The expression and distribution of CXCL12 or CXCR4 were examined by immunofluorescence staining and western blot. The effects of CXCL12 rat peptide, CXCL12 neutralizing antibody, CXCR4 antagonist, and astrocyte metabolic inhibitor on pain hypersensitivity were explored by behavioral tests in naive or SNL rats. We measured the expression level of c‐Fos and CGRP to evaluate the sensitization of neurons by RT‐PCR. The activation of astrocyte and microglia was analyzed by measuring the level of GFAP and iba‐1. The mRNA levels of the pro‐inflammatory cytokines such as TNF‐α, IL‐1β, and IL‐6 and Connexin 30, Connexin 43, EAAT 1, EAAT 2 were also detected by RT‐PCR. RESULTS: First, we found that the expression of CXCL12 and CXCR4 was upregulated after SNL. CXCL12 was mainly expressed in the neurons while CXCR4 was expressed both in astrocytes and neurons in the spinal dorsal horn after SNL. Moreover, intrathecal administration of rat peptide, CXCL12, induced hypersensitivity in naive rats, which was partly reversed by fluorocitrate. In addition, the CXCL12 rat peptide increased mRNA levels of c‐Fos, GFAP, and iba‐1. A single intrathecal injection of CXCL12 neutralizing antibody transiently reversed neuropathic pain in the SNL rat model. Consecutive use of CXCL12 neutralizing antibody led to significant delay in the induction of neuropathic pain, and reduced the expression of GFAP and iba‐1 in the spinal dorsal horn. Finally, repeated intrathecal administration of the CXCR4 antagonist, AMD3100, significantly suppressed the initiation and duration of neuropathic pain. The mRNA levels of c‐Fos, CGRP, GFAP, iba‐1, and pro‐inflammatory cytokines, also including Connexin 30 and Connexin 43 were decreased after injection of AMD3100, while EAAT 1 and EAAT 2 mRNAs were increased. CONCLUSION: We demonstrate that the CXCL12/CXCR4 signaling pathway contributes to the development and maintenance of neuropathic pain via central sensitization mechanisms. Importantly, intervening with CXCL12/CXCR4 presents an effective therapeutic approach to treat the neuropathic pain.